Imperative Role of Technology Intervention and Implementation for Automation in the Construction Industry - Amit Srivastava; Sajjaf Jawaid; Rajesh Singh; Anita Gehlot; Shaik Vaseem Akram; Neeraj Priyadarshi; Baseem Khan (Advances in Civil Engineering)
According to sustainable development goals, the construction industry is one of the vital industries that can build resilient and sustainable infrastructure for human settlements. As the traditional approaches in the construction industry are causing distinct challenges including environmental pollution and excess energy usage, however, the integration of emerging technologies will assist us to reduce the impact and also enhance the activities in the construction industry. Motivated by the facts, this study aims to address the significance of automation in the construction industry with distinct emerging technologies like the Internet of things (IoT), automation, radio frequency identification (RFID), building information modeling (BIM), augmented reality (AR), and virtual reality (VR). The large amount of data generated from the IoT, RFID, BIM, and AR/VR provided an opportunity for big data and artificial intelligence (AI) to extract meaningful insights related to the events in the construction industry. Furthermore, edge and fog computing technology encourages us to implement AI at the edge network for analytics at the end of the edge device. Based on the above analysis, the article discussed recommendations that could assist in further enhancement and implementation of automation in the construction industry. Cloud-assisted AR/VR, integration of AI with IoT infrastructure, 4D printing, adopting blockchain in the construction industry, and smart robotics are the recommendation addressed in this article.